Engagement of Agricultural, Technical and Vocational Education and Training (ATVET) Institutions - Egeru, Anthony; Nakayiwa, Florence; Recha, John W.M.; Kawira, Tracy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Egerton University, a member university of the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM), held an engagement meeting with Technical Vocational Education and Training (TVET) institutions on 6th May 2022. The meeting was held under the auspices of the University-TVET forum. This forum sought to enhance the collaboration and working partnership between universities and TVET institutions to strengthen the education value chain. The UniversityTVET forum is part of an arrangement championed under the RUFORUM's Transforming African Agricultural Universities to meaningfully contribute to Africa's growth and development (TAGDev) programme.